Comparing the Efficacy of a Nurse-Driven and a Physician-Driven Diabetic Ketoacidosis (DKA) Treatment Protocol - Anis TR; Boudreau M; Thornton T (Dove Medical Press, 2021)
Takla R Anis,1 Marybeth Boudreau,1 Tyson Thornton2 1Pharmacy Department, Northern Light Eastern Maine Medical Center, Bangor, ME, USA; 2Pharmacy Department, Northern Light Sebasticook Valley Hospital, Pittsfield, ME, USACorrespondence: Takla R AnisPharmacy Department, Northern Light Eastern Maine Medical Center, Bangor, ME, 04401, USAEmail takla.anis@gmail.comBackground: Standardized DKA treatment could result in better overall safety and efficacy outcomes. The primary objective of this study is to validate the efficacy of an adapted nurse-driven DKA protocol compared to a physician-driven DKA protocol across the continuum of three hospital settings: the University of Colorado upon which the physician-driven protocol is based, Northern Light Eastern Maine Medical Center (NLEMMC), and Northern Light Sebasticook Valley Hospital (NLSVH). The secondary objective is to assess the safety of the adapted nurse-driven DKA protocol adapted at NLEMMC and NLSVH through determining the incidence of hypoglycemia and anion gap reopening.Patients and Methods: This was a retrospective, IRB-approved, multi-center study that included: patients 18 years or older who were treated with the DKA protocol at NLEMMC or NLSVH, and admitted to the emergency department between July 2015 and October 2020 with a primary diagnosis of DKA and an elevated anion gap greater than or equal to 13 mEq/L.Results: A total of 90 patients from NLEMMC and 64 patients from NLSVH were included and compared to 111 patients from the University of Colorado who were included in the post protocol implementation group. There was no statistically significant difference in the primary outcome, time to anion gap closure, between the original University of Colorado study (10.3 hours) and the NLEMMC (10.9 hours, p = 0.420) and NLSVH (8.8 hours, p = 0.115) results presented in this study.Conclusion: The standardized nurse-driven DKA treatment protocol at NLEMMC and NLSVH showed no statistical difference in time to anion gap closure compared to the University of Colorado study upon which it was based. This finding is particularly relevant to hospitals such as NLEMMC and NLSVH that lack provider resources and teams of endocrinologists required for the physician-driven DKA protocol.Keywords: diabetic ketoacidosis, protocol, treatment